Description of two new species of annual fishes of the Hypsolebias antenori species group (Cyprinodontiformes: Rivulidae), from Northeast Brazil - Britzke, Ricardo; Nielsen, Dalton T. B.; Oliveira, Claudio (Zootaxa, 2016)
The Hypsolebias antenori species group comprises a monophyletic clade of annual fishes occurring in the semi-arid region of Northeastern Brazil. Most species of this group are found in the Rio São Francisco basin, but there are three species that inhabit small coastal basins. Hypsolebias faouri new species, is described from a temporary pool located near Rio Preto, a tributary of the Rio São Francisco, and Hypsolebias martinsi new species, is described from an annual pool near Rio Icaraizinho, a coastal drainage. Molecular data corroborates the monophyly of Hypsolebias and both new species.